[OP.4B.01] LEFT VENTRICULAR MECHANICS IN PATIENTS WITH MASKED HYPERTENSION. (September 2016) - Tadic, M.; Cuspidi, C.; Vukomanovic, V.; Pencic, B.; Kocijancic, V.; Celic, V.
Abstract : Objective: We sought to investigate left ventricular (LV) mechanics in subjects with masked hypertension (MH), normotensive and sustained hypertensive patients. Design and method: This cross-sectional study included 209 untreated subjects who underwent 24-hour ambulatory BP monitoring and complete two-dimensional echocardiographic examination (2DE) including multilayer strain analysis. MH was diagnosed if clinic blood pressure (BP) was normal (<140/90 mmHg) and 24-hour BP was increased (> = 130/80 mmHg). Results: According to criteria provided in the Methods, the study sample included 62 normotensive subjects (30%), 64 MH (30%) and 83 sustained hypertensives (40%). 2DE LV longitudinal strain gradually and significantly decreased from normotensive controls across MH individuals to sustained hypertensive patients (−21.3 ± 2.1 vs. −19.1 ± 2 vs. −17.4 ± 1.8 %, p < 0.001). The same is valid for 2DE LV circumferential strain (−21.9 ± 2.9 vs. −20 ± 2.5 vs. −18.4 ± 2.2 %, p < 0.001). 2DE radial strain was not different between groups. 2DE LV longitudinal endocardial and mid-myocardial layer strains progressively decreased from normotensive control to sustained hypertensive individuals (−26.4 ± 4.6 vs. −23.8 ± 3.8 vs. −21 ± 3.6 %, p < 0.001 for endocardial strain; and −21 ± 3.2 vs. −18.8 ± 2.8 vs. −16.8 ± 2.5 %, p < 0.001 for mid-myocardial strain). Similar results were obtained for 2DE LV circumferential endocardial and mid-myocardial layer strains (−28.6 ± 5 vs. −25.4 ± 4.4 vs. −23.2 ± 4 %, p < 0.001 for endocardial strain; and −21.5 ± 2.8 vs. −19.4 ± 2.4 vs. −18.2 ± 2.2 %, p < 0.001 for mid-myocardial strain). Longitudinal and circumferential epicardial layer strains were decreased in sustained hypertensive patients than in normotensive controls. 24-hour systolic BP was associated with peak 2DE LV longitudinal (β = −0.442, p < 0.001), endocardial strain (β = −0.394, p < 0.001), mid-myocardial strain (β = −0.426, p < 0.001) and 2DE circumferential endocardial strain (β = −0.364, p < 0.001) in the whole study population independent of LV mass index and E/e' ratio. Conclusions: MH significantly influences LV deformation assessed by 2DE traditional strain and 2DE multilayer strain. 24-hour systolic BP is associated with LV deformation evaluated with comprehensive 2DE strain analysis independent of LV structure and diastolic function.